THE IMPACT OF DIGITAL RESILIENCE ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORKFORCE AGILITY AMONG HOSPITAL EMPLOYEES - Adhietya Widyaningrum; Kosasih; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The rapid advancement of digital transformation in healthcare organizations has increased the need for employees to adapt to technological changes while maintaining high levels of performance. In this context, digital resilience and workforce agility have emerged as critical capabilities that enable employees to effectively respond to dynamic and technology-driven work environments. This study aims to examine the impact of digital resilience on employee performance and investigate the mediating role of workforce agility among hospital employees. This research employed a quantitative approach using an explanatory survey design. Data were collected from 100 employees of Hospital X through a structured questionnaire distributed to employees who actively utilized digital systems in their daily work activities. The collected data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, F-test, t-test, coefficient of determination (R²), and mediation analysis using the Sobel Test. Statistical analysis was conducted using SPSS version 26. The study concludes that Digital Resilience and Workforce Agility are important determinants of Employee Performance in healthcare organizations. Strengthening employees' digital adaptability and agility can contribute to improved workforce effectiveness and support the successful implementation of digital transformation initiatives in hospitals. These findings provide valuable insights for hospital management in designing strategies aimed at enhancing employee capabilities and organizational performance in the digital era.